Peptida Bioaktif Kasein Susu Kambing sebagai Agen Antibakteri terhadap Staphylococcus aureus - Diana lestari; Eddyson Giordan (JURNAL AGROINDUSTRI HALAL, 2020)
Goat milk is widely consumed as a functional food. Milk’s derived bioactive peptides are the specific peptides which are produced by the degradation of milk protein by proteases enzyme and posseses a different positive properties such as antihypertensive, antioxidant, antibacterial, antiiflamatory and many more. The purpose of this research is to explore the antibacterial activity of fractionated bioactive peptides derived from the hydrolysis of goat milk casein and identify the peptide profiles using SDS-PAGE electrophoresis. Casein was isolated from fresh goat milk and then hydrolyzed by crude bromelain enzyme with an activity of 0.420 U/mL for 0, 1, 2, and 3 minutes at a temperature of 50oC. Profile analysis from bromelain hydrolyzates showed some protein bands with molecular weights from about 6.63 kDa to 7.32 kDa on SDS PAGE gel. The fractionation process was carried out on selected bromelain hydrolyzates using a 30 kDa and 10 kDa membrane Cut-Off. The antibacterial test results showed that the hydrolysates from B0 and B1 peptides showed inhibitory activity on Staphylococcus aureus. The fractionation process increased the antibacterial activity of hydrolysates from peptides B0 and B1. Small molecular weight peptides have better inhibitory activity.